KRITIK KOMERSIALISASI PRODUK MURABAHAH: KEUNTUNGAN BISNIS VS TUJUAN SYARIAH - Siti Padilah Ramadani; Ikhwan Muzaki; Julia Handayani; Ahmad Tibrizi; Mukhlishotul Jannah (Jurnal Ekonomi dan Bisnis, 2025)
This study critically analyzes the commercialization of Murabahah products in Islamic financial institutions in Indonesia. The research focuses on the imbalance between profit-oriented practices and the fundamental objectives of Sharia, which emphasize justice, transparency, and trustworthiness. Using a qualitative literature review method, this study explores the concept of Murabahah, its implementation in Islamic banking, the use of wakalah, the phenomenon of side-streaming, and academic as well as practitioner criticism regarding Murabahah’s dominance in financing portfolios. The findings indicate that Murabahah practices often deviate from DSN-MUI fatwas, particularly regarding ownership transfer, inappropriate use of murabahah bil wakalah, and margin determination based on interest rate benchmarks. These deviations risk transforming Murabahah into a conventional financing instrument with a disguised mark-up scheme. This study recommends strengthening Sharia compliance, enhancing price transparency, improving internal procedures, increasing public literacy, and harmonizing regulations to realign Murabahah with maqashid al-shariah.